السياق ودوره في تحديد دلالات الأصوات المكتوبة: The Context and Its Role in Specifying of Phrased Voices’ Significances (Al-Qamar, 2021)
This article attempts a systemic discussion of the basic principles and fundamentals that would help discover the meaning enshrined in a word or sentence and determine their semantic value in the context of a single sentence or the book at large. This is what is known as context which forms the basis for the understanding of the intended meaning of the writer. This is very important because the reader will not be able to grasp the exact or proper meaning of a text merely by reading it on its facial value without having requisite information about the context or events or other situational evidence or any other issue that may help in a proper understanding of the text.
Keywords: Context; Phrased Voices; Significances